Prospects for the Application of Tryptanthrin and Mostotrin Alkaloids in Therapy and Control of Inter-Specific Interactions in Various Symbiotic Systems: A Review - Alekleksandr Popov; Tatyana Rutckova; Olga Styshova; Andrey Shchekotikhin; Valentin Stonik (Chemistry and Biochemistry: Research Progress Vol. 6, 2025)
Tryptanthrin (TR) is one of the most widespread and well-known quinazolinone alkaloids with cytotoxic, antimicrobial and immunomodulatory efficiencies. This secondary metabolite exhibits a large area of biological activity, generating an increasing interest in the synthesis and evaluation of its derivatives and analogues. As main natural sources are known plant species like Polygonum tinctorium and other indigo plants. Currently, a lot of attention has been paid to the studies on the possible bio-regulatory role of TR. Mostotrin (MT) is a synthetic water-soluble analogue of TR, which can expand the spectrum of pharmaceuticals for the treatment of inflammatory, antitumor, infectious diseases, and recently emerging epidemics like SARS-CoV-2. TR and MT derivatives even have capacity for use as important elements of signalling control in inter-species or inter-kingdom relationships of various multi-member microbiomes (community of microorganisms in e.g. the human body) with the host organisms and interactions of microorganisms in diverse marine or earth ecosystems. Recently published studies on the biological activity and probable molecular mechanisms underlying the therapeutic and regulatory actions of TR and MT became the subject of analysis in this mini-review.